Pengaruh Prosedur Pembayaran Gaji PNS terhadap Kepuasan Nasabah pada Bank Mandiri Taspen Kantor Cabang Ujung Berung - Salsa Bella; Widwi Handari Adji; Salsa Yulia Gustina (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study is to find out the effect of salary payment procedures on customer satisfaction at Bank Mandiri Taspen Ujung Berung. By using quantitative methods descriptive approach with data collection as well as observations, questionnaires, and documentation. The population taken is customers at Bank Mantap itself in the city of Bandung, the sample taken is 95 respondents. Primary data was obtained using a questionnaire and processed using SPSS V.24 software for windows. T test results with the value of the regression line equation Y' = 62.586 + 0.064X and the correlation test results are 0.048. For the test results, the coefficient of determination of the test found the calculated F value of 0.212 with Sig. of 0.000. Therefore the value of sig. < 0.05 then Ho is rejected, which means that there is an effect of the PNS pension payment procedure on customer satisfaction. Problems in online services are not optimal, so it is necessary to increase employee understanding and skills in providing online services. Keywords: Procedure, Payment, Customer Satisfaction